TINGKAT KEPATUHAN PEDAGANG BESAR PASAR ANTASARI DAN PASAR HARUMANIS ATAS PAJAK PENGHASILAN (PPh) PASAL 21 PADA KOTA BANJARMASIN TAHUN 2022 - Riska Aulia Noor (JURNAL LENTERA AKUNTANSI, 2022)
The problem raised in this study is the level of corporate taxpayer compliance with the tax law regarding income tax article 21. This research uses a descriptive comparative research type, namely research that aims to provide an overview of the comparison of compliance of wholesalers in Antasari market and Harum Manis market Banjarmasin on Income Tax (PPh) article 21. The test results were carried out using the separated variance t-test (independent sample test). The results showed that the level of tax compliance for wholesalers of the Antasari market in the category of tax compliance levels for wholesalers of the Harum Manis market had a high level of tax compliance. The tax compliance of the wholesalers of the Antasari market and the Harum Manis market has a significant difference, where the level of tax compliance on income tax for the traders of the Harum Manis market has a higher level of compliance than the level of compliance held by the wholesalers of the Antasari market.Keywords: Income Tax, Tax Compliance